Kedudukan Pihak Ketiga Dalam Proses Penyelesaian Sengketa Di Pengadilan Tata Usaha Negara (Studi Kasus Perkara Nomor: 23/G/2015/PTUN.DPS) - Kadek Dwi Fitriyani; Ida Ayu Putu Widiati; I Made Minggu Widyantara (Fakultas Hukum Universitas Warmadewa, 2019)
In state administrative disputes has ditermined who can sue and who can be sued. But aside from the plaintiff and the defendan, in a state administrative dispute lawsuit it is possible for everyone with an interest in the dispute to participate or be include in the vetting process. The formulation of the problems are 1) How the mechanism of the inclusion of the third party in the process of dispute resolution in the state administrative court. 2) How the legal consequences of the inclusion of the third party in the case number 23/G/2015/PTUN.DPS. This research is a normative legal research with the problems approach are statute approach and case approach. Everyone who has an interest can be include in a state administrative dispute. The inclusion of the intervention can be due to their self, the wishes of either party or the initiative of the judge. The entry of the intervention gave the intervention the same obligations and rights with the parties. In case number. 23/G/2015/PTUN.Dps the intervention is placed as a defendant II intervention because of the interest that it has the same as the defendant. And that make the third party has the same obligation and the rights as those of the defendant.